The Role of Sales Promotion Girls as Frontliners in Wardah's Product Marketing Strategy - Hulu, Nutiwati; Lubis, Karina Safitri; Khairunnisa, Khairunnisa; Manurung, Karina; Ovianti, Widya; Syahreza, Dina Sarah; Aprinawati, Aprinawati (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This research analyzes the role of the Sales Promotion Girl (SPG) as a frontliner in the marketing strategy for Wardah products, one of the leading cosmetic brands in Indonesia. Using qualitative methods through in-depth interviews and observations, this research found that SPG has a significant contribution in increasing brand awareness, customer loyalty and product sales effectiveness. The research results also reveal that communication skills, adaptation to digital marketing trends, and collaboration with the marketing team are key factors for SPG's success in achieving marketing targets. This research suggests the importance of ongoing training, attention to SPG welfare, and strengthening cross-functional collaboration to increase the effectiveness of SPG's role in supporting Wardah's marketing strategy.